Histologic and immunohistochemical evaluation of mirror image biopsies in oral squamous cell carcinoma - Vineet Gupta; Pratibha Ramani (Elsevier, 2016)
Background and objective: The concept of field cancerization has frequently been quoted to explain the occurrence of multiple primary cancers in the head and neck region and recurrence following complete excision of the original tumor. The main objective is to study the occurrence of field changes in mirror image biopsy in relation to histopathological changes in the oral mucosa among oral cancer patients using hematoxylin and eosin and to study the expression pattern of cytokeratin, Ki-67 and p53 in oral squamous cell carcinoma and mirror image biopsy. Materials and methods: A pilot study of 15 patients clinically diagnosed with carcinoma lesion and their corresponding mirror image sites were taken and stained using immunohistochemistry method for the expression of cytokeratin, Ki-67 and p53. Results: Primary tumors showed strong positive staining for cytokeratin throughout both the epithelium and malignant epithelial islands but absence of staining for Ki-67 and p53. Conclusion: CK may be useful in predicting epithelial differentiation and Ki-67 and p53 act as weak indicators of malignant disease progression in oral tissues.